Trigeminal Nerve Injuries - Miloro, Michael. (Springer Berlin Heidelberg : Imprint: Springer, 2013)
Trigeminal nerve injuries present complex clinical challenges and can be very distressing for patients, resulting in abnormal sensations of the oro-facial region with episodes of unpleasant paresthesia and interference with activities of daily living. Since these injuries are frequently caused by surgical or dental procedures, patients may seek legal counsel as a result of their injury. Most surgeons, however, do not evaluate and manage patients with trigeminal nerve injuries on a regular basis, and may lack the knowledge and skills required for optimal patient management based upon the specific nerve injury. Trigeminal Nerve Injuries is the first to be devoted to the comprehensive diagnosis and management of trigeminal nerve injuries. A wide range of topics are covered by experts in the field of microneurosurgery, including historical perspectives, demographics, etiology, anatomy and physiology, pathophysiology and mechanisms of injury, clinical neurosensory testing, nonsurgical management, and surgical management and principles of microneurosurgery, specifically involving the inferior alveolar and lingual nerves. Algorithms and a glossary are provided that will assist in the clinical management of these complex scenarios. The authors include surgeons with considerable experience in the field who have previously published on the subject. This book will serve as an ideal clinical reference for surgeons with patients who sustain trigeminal nerve injuries.